Comprehensive analysis of vaginal microbiota, metabolites, and inflammatory factors in preterm and term pregnancies - Shen, Li-Ping; Cai, Bei-Jun; Guan, Jing-Xue; Peng, Ting; Jin, Lei (Frontiers in Microbiology, 2025)
PurposeThis study aimed to reveal the interrelationships among vaginal microorganisms, metabolism, and inflammatory factors in premature pregnant women.MethodsA total of 77 pregnant women were enrolled and divided into a preterm birth group (n = 23) and a full-term birth group (n = 54) according to the gestational week of delivery. Blood samples and vaginal secretion samples were collected before the onset of labor or after rupture of membranes for blood index testing, 16S RNA sequencing of vaginal secretion samples, and untargeted metabolite determination.ResultsCompared with the full-term group, the preterm group exhibited significantly elevated inflammatory markers (SII 689 vs. 1,061, p < 0.001) and decreased vaginal microbiota α diversity (Shannon index 3.56 vs. 2.65). Meanwhile, the abundance of Firmicutes was increased (54.96% vs. 76.73%), primarily comprising Lactobacillus jensenii, which was negatively correlated with gestational week; metabolomics identified 83 significantly differential metabolites, including upregulated tyrosine-arginine, cholesterol sulfate, and benzene compounds such as 2,4-dichlorophenol. KEGG analysis revealed that pathways such as kynurenine, steroids, lipids, and microbial metabolism were significantly activated in the preterm birth group. Omics association analysis revealed significant correlations among microbiota, metabolites, and inflammatory markers. For example, Lactobacillus jensenii and inflammatory metabolites such as arginine-lysine, sulfamethoxazole, 5-aminovaleric acid, and epoxiconazole were all positively correlated with SII (p < 0.05).ConclusionThe results suggest that an imbalance in vaginal microbiota, particularly the abnormal proliferation of Lactobacillus jensenii, as well as amino acid and lipid metabolism may be associated with inflammation-induced preterm birth.